Influence of Minor Additives on the Performance of Calcined Clay and Blast Furnace Slag Based One Part Alkali-Activated Mortars - Calbiyik, Suat; Omur, Tarik; Ozkan, Hakan; Kabay, Nihat (MDPI, 2025)
The availability of key precursors of alkali-activated binder (AAB) systems is declining, requiring sources. Calcined clays (CCs) stand out as a promising alternative due to their widespread accessibility. Although the properties of CC and blast furnace slag (BFS)-based two-part AABs have been well reported in the literature, the effect of minor additives on the properties of a one-part AAB system composed of CC and BFS remains unexplored. In this research, calcined magnesia (CM), aerial lime (AL), hydraulic lime (NHL), quicklime (QL), borax (BR), and zeolite (ZP) have been used as minor additives and incorporated into the AAB system at between 2% and 15%. The specimens were activated with sodium-metasilicate, and the fresh, physical, mechanical, durability and microstructural properties of mortars have been investigated. Key findings indicate that all minor additives, except for BR, enhanced the early- and later-age mechanical properties. Notably, 10% QL addition significantly increased compressive strength by up to 55% at 28 days (50.9 MPa), compared to the reference. BR and ZP usage eliminated the efflorescence formation without compromising other properties. Furthermore, incorporating QL, AL, CM, and BR markedly reduced the chloride permeability of the mortars and decreased Dnssm value by as much as 81%, compared to the reference.
Keywords: calcined clays; blast furnace slag; one-part alkali-activation; efflorescence; quicklime; borax; calcined magnesia; chloride migration; GEOPOLYMER; CEMENT; HYDRATION; MINERALS; ZEOLITE; BINDERS; Construction & Building Technology; Engineering